Junior High School Educators' Strategies for Making Inclusive Education Policy a Working Tool in the Kadjebi District, Ghana (Global Journal of Human-Social Science, 2025)
Abstract not found
Keywords: disability; education; educators; inclusion; inclusive; policy; special education; strategy